Production of antihypertensive and antidiabetic peptide fractions from quinoa (Chenopodium quinoa Willd.) by electrodialysis with ultrafiltration membranes - Adrián González-Muñoz; Marion Valle; Rotimi E. Aluko; Laurent Bazinet; Javier Enrione (Food Science and Human Wellness)
Processing bioactive peptides from natural sources using electrodialysis with ultrafiltration membranes (EDUF) have gained attention since it can fractionate in terms of their charge and molecular weight. Quinoa is a pseudo-cereal highlighted by its high protein content, amino acid profile and adapting growing conditions. The present work aimed at the production of quinoa peptides through fractionation using EDUF and to test the fractions according to antihypertensive and antidiabetic activity. Experimental data showed the production of peptides ranging between 0.4 and 1.5 kDa. Cationic (CQPF) (3.01 %), anionic (AQPF) (1.18 %) and the electrically neutral fraction quinoa protein hydrolysate (QPH)-EDUF (∼95 %) were obtained. In-vitro studies showed the highest glucose uptake modulation in L6 cell skeletal myoblasts in presence of QPH-EDUF and AQPF (17 % and 11 %) indicating potential antidiabetic activity. The antihypertensive effect studied in-vivo in spontaneously hypertensive rats (SHR), showed a decrease in systolic blood pressure in presence of the fractionated peptides, being 100 mg/kg a dose comparable to Captopril (positive control). These results contribute to the current knowledge of bioactive peptides from quinoa by reporting the relevance of EDUF as tool to produce selected peptide fractions. Nevertheless, further characterization is needed towards peptide sequencing, their respective role in the metabolism and scaling-up production using EDUF.